2008
DOI: 10.1007/bf03349256
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism is associated with increased myostatin expression in rats

Abstract: Besides its key role in the regulation of muscle growth during development, myostatin also appears to be involved in muscle homeostasis in adults, and its expression is upregulated during muscle atrophy. Since muscle physiology is greatly influenced by thyroid status, and the myostatin promoter region contains several putative thyroid hormone response elements, in the present study we examined the possible role of thyroid hormones in the regulation of myostatin gene expression. Adult male rats were made either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…This differential modulation indicates that the presence of TH at physiological concentrations is essential for the establishment of some biological processes, as demonstrated by proinsulin mRNA expression. Indeed, these data agree with reports that showed an increase of myostatin gene expression in hypothyroid rats, even though no changes in myostatin mRNA levels were detected in L-T4-treated rats (31). However, the mechanisms underlying these alterations, observed only in the hypothyroid condition, are unknown.…”
Section: Discussionsupporting
confidence: 91%
“…This differential modulation indicates that the presence of TH at physiological concentrations is essential for the establishment of some biological processes, as demonstrated by proinsulin mRNA expression. Indeed, these data agree with reports that showed an increase of myostatin gene expression in hypothyroid rats, even though no changes in myostatin mRNA levels were detected in L-T4-treated rats (31). However, the mechanisms underlying these alterations, observed only in the hypothyroid condition, are unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Another possibility is that prolonged T 3 treatment in cells is needed to achieve results similar to those observed in animal models. Of note, studies in which T 3 acute effect is not the aim usually perform treatments for no longer than 24 h (55, 56). …”
Section: Discussionmentioning
confidence: 99%
“…A research on the 5’-terminal regulatory region of the myostatin gene revealed various agents possibly acting as transcriptional factors, such as myocyte enhancing factor 2 (MEF2), peroxisome proliferator-activated receptor gamma (PPARγ), MyoD and NF-κB, as well as a mechanism for myostatin upregulation by glucocorticoids [ 62 ]. Myostatin gene expression was also found to be affected by tumor necrosis factor -α (TNF-α), hormones (such as insulin-like growth factor (IGF-1), angiotensin II and thyroid hormones), nutritional supplementation, hyperammonemia, physical exercise and hypoxia [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Furthermore, myostatin was found to down-regulate its expression in a self-regulatory loop [ 71 ].…”
Section: Introductionmentioning
confidence: 99%